2021
DOI: 10.1016/j.pneurobio.2020.101953
|View full text |Cite
|
Sign up to set email alerts
|

Increased telomerase improves motor function and alpha-synuclein pathology in a transgenic mouse model of Parkinson’s disease associated with enhanced autophagy

Abstract: Highlights Telomerase activators (TA) increase Tert expression in brains of a PD mouse model. Activator treatment improves PD motor symptoms: gait and balance. Activators reduce different forms of alpha-synuclein in brains of transgenic mice. Decreased autophagy markers LC3 and p62 suggest a better protein degradation. Our preclinical data suggest a use of TA to ameliorate PD-like sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 70 publications
0
36
0
1
Order By: Relevance
“…In the development of PD, the regulation of autophagy is essential (Zhu et al, 2019;Wan et al, 2020). The damage to the autophagy pathway and the resulting accumulation of misfolded α-synuclein and other proteins aggregates represent the common pathobiological characteristics of neurodegenerative diseases such as PD (Erb and Moore, 2020;Kwon et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In the development of PD, the regulation of autophagy is essential (Zhu et al, 2019;Wan et al, 2020). The damage to the autophagy pathway and the resulting accumulation of misfolded α-synuclein and other proteins aggregates represent the common pathobiological characteristics of neurodegenerative diseases such as PD (Erb and Moore, 2020;Kwon et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Wan and colleagues applied both activators, TA-65 and GRN510, in a pilot study on two-year-old female mice for 3 months which resulted in a significant increase of mTert expression in brain tissue [ 67 ]. Analysing motor coordination as a read-out for age-related brain function, the study found a significant improvement of strength and coordination in a static rod test where both treatments increased the time on the rod similarly to that of adult (10 months old) mice while only that for GRN510 was statistically significant [ 67 ]. These results are similar to those described by Eyolfson and co-authors who treated rats for one month with TA-65 before inflicting a brain injury.…”
Section: Increasing Telomerase/tert Levels In Ageing Brain and As Therapy For Neurodegenerationmentioning
confidence: 99%
“…Both activators significantly increased mTert gene expression in both sexes after 14 months of treatment starting at 4 months. Additionally, in vitro experiments on cultured primary embryonic mouse neurons at a time point where these neurons were no longer positive for telomerase activity [ 41 ] confirmed specifically that neurons were able to upregulate mTert expression after activator treatment [ 67 ].…”
Section: Increasing Telomerase/tert Levels In Ageing Brain and As Therapy For Neurodegenerationmentioning
confidence: 99%
See 2 more Smart Citations